4-Aminobenzoic Acid Derivatives: Converting Folate Precursor to Antimicrobial and Cytotoxic Agents - Krátký, Martin; Konečná, Klára; Janoušek, Jiří; Brablíková, Michaela; Janďourek, Ondřej; Trejtnar, František; Stolaříková, Jiřina; Vinšová, Jarmila (Biomolecules, 2019)
4-aminobenzoic acid (PABA), an essential nutrient for many human pathogens, but dispensable for humans, and its derivatives have exhibited various biological activities. In this study, we combined two pharmacophores using a molecular hybridization approach: this vitamin-like molecule and various aromatic aldehydes, including salicylaldehydes and 5-nitrofurfural, via imine bond in one-step reaction. Resulting Schiff bases were screened as potential antimicrobial and cytotoxic agents. The simple chemical modification of non-toxic PABA resulted in constitution of antibacterial activity including inhibition of methicillin-resistant Staphylococcus aureus (minimum inhibitory concentrations, MIC, from 15.62 µM), moderate antimycobacterial activity (MIC ≥ 62.5 µM) and potent broad-spectrum antifungal properties (MIC of ≥ 7.81 µM). Some of the Schiff bases also exhibited notable cytotoxicity for cancer HepG2 cell line (IC50 ≥ 15.0 µM). Regarding aldehyde used for the derivatization of PABA, it is possible to tune up the particular activities and obtain derivatives with promising bioactivities.
Keywords: kyselina listová; viabilita buněk; Methicillin-Resistant Staphylococcus aureus; buňky Hep G2; Hep G2 Cells; Cytotoxins; Folic Acid; cytotoxicity; cytotoxiny; Humans; Schiff bases; antibacterial activity; synthesis; 4-aminobenzoic acid; Microbial Sensitivity Tests; 4-Aminobenzoic Acid; Anti-Bacterial Agents; kyselina 4-aminobenzoová; methicilin rezistentní Staphylococcus aureus; Cell Survival; lidé; mikrobiální testy citlivosti; antibakteriální látky; vitamin; antifungal activity